(untitled) (Bangladesh Medical Journal, 2009)
Tobacco consumption is harmful to health, and is one of the main causes of death in worldwide. It is evident that the prevalence of tobacco consumption is raising in most of low and middle income countries. Considering this, a cross sectional study was conducted in a selected urban area of southern Bangladesh with a view to assessing the prevalence of tobacco consumption and factors affecting the use of tobacco use. Multistage cluster sampling technique was adopted to select the urban ward and the respondents were selected systematically. A total of 399 respondents were interviewed face to face using a semi-structured interview schedule. Analysis shows that 30% of the population of aged 18 years above were currently using tobacco of any form. The mean age of starting tobacco use was 18.8 years. The most frequent form of tobacco use was smoking cigarette followed by Zarda with betal quid. Multivariate analysis revealed that illiterate respondents were 3.3 times more tobacco users than their educated counterparts. It was also higher among the Muslims (OR=4.979; 95% CI=1.255-19.754). Tobacco use was also high among the labourer (OR=8.541; 95% CI=2.422-30.120) and businessmen (OR=7.727, 95% CI=2.501-23.875). However, no statistically significant association was found between current tobacco use and age, sex, housing condition and knowledge on tobacco use (p>0.05). The finding of this study suggests that as tobacco use is more prevalent among the poor and illiterate segment of the population, strong implementation of anti-tobacco legislation is warranted. DOI: 10.3329/bmj.v38i2.3573 Bangladesh Medical Journal 38(2) 2009 48-52